Kesiapan Perusahaan di Indonesia Dalam Menghadapi Revolusi Industri 4.0 - Idham Mahriv; Nisa Alifatuzzahra; Nurbaiti Nurbaiti (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The main point or The purpose of this study is to find out and understand the preparations that every business company in Indonesia has had to face and will continue to face regarding the current era of industrial revolution 4.0 underway and is currently starting to face further developments in the era that is starting Entering era of industrial revolution 5.0. Industrial Revolution 4.0 or what is also known as "cyber physical systems" is an event where there is cooperation between and automation technology and cyber technology. So with the evolution of industry, in the current era, companies previously needed manpower and human resources with physical abilities who could be productive in large amounts of energy, now with chanwith the changes that occur in the eras that occur in industrial sector, technology has entered as a component that helps human work, inseparable from Therefore, the impact is widespread, especially in the industrial sector in Indonesia. Now many companies have implemented technology-based digital systems to support their performance to be more productive and generate large profits as well as develop innovation and facilitate the company's progress to continue to be sustainable in the future. Technology is developing and advancing rapidly thanks to scientists and researchers who have contributed to it in terms of science and technology. With this, digital-based systems and digital-based physical facilities and infrastructure created to make things easier for people achieve various needs and desires according to their respective goals. This is certainly something that cannot be denied and avoided in the world community, not only in Indonesia. Therefore, this article will focus on discussing the readiness of companies in Indonesia to face the positive and negative challenges arising from changes in this progress Results of this study article conclude that although there are efforts being made to prepare companies in Indonesia to face the Industrial Revolution 4.0, further efforts are still needed to ensure equal readiness in various industrial sectors.